2012
DOI: 10.1152/jn.00510.2011
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of intrinsic properties and synaptic inputs to motoneuron discharge patterns: a simulation study

Abstract: Powers RK, ElBasiouny SM, Rymer WZ, Heckman CJ. Contribution of intrinsic properties and synaptic inputs to motoneuron discharge patterns: a simulation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
114
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(131 citation statements)
references
References 65 publications
10
114
2
5
Order By: Relevance
“…When applying "proportional inhibition" (an inhibitory input that rose and fell in parallel with the excitatory input; also referred to as "balanced inhibition"; Berg et al 2007), with the inhibitory conductance applied uniformly across the soma and dendrites ( Fig. 7 panel 2, in Powers et al 2012), the low-rate modulation observed closely resembles that which we have observed in the spastic-paretic limb of stroke survivors (Figs. 1 and 4).…”
Section: Pic-based Mechanisms For Saturation In Motor Unit Firing Ratsupporting
confidence: 55%
See 3 more Smart Citations
“…When applying "proportional inhibition" (an inhibitory input that rose and fell in parallel with the excitatory input; also referred to as "balanced inhibition"; Berg et al 2007), with the inhibitory conductance applied uniformly across the soma and dendrites ( Fig. 7 panel 2, in Powers et al 2012), the low-rate modulation observed closely resembles that which we have observed in the spastic-paretic limb of stroke survivors (Figs. 1 and 4).…”
Section: Pic-based Mechanisms For Saturation In Motor Unit Firing Ratsupporting
confidence: 55%
“…This mechanism would produce saturation at a relatively low firing rate. In animal preparations, however (Lee and Heckman 1998;Powers et al 2012), PIC activation alone does not produce the strong saturation seen in the present results, as demonstrated by the observed prolonged period of flat or even negative firing rate modulation.…”
Section: Pic-based Mechanisms For Saturation In Motor Unit Firing Ratcontrasting
confidence: 50%
See 2 more Smart Citations
“…In vertebrate smooth muscle, neuromodulators act directly on the muscle (Burnstock 1985). In skeletal muscle, persistent inward currents in motor neuronal dendrites are modulated by serotonin and norepinephrine (Heckman et al 2008) and, given appropriate excitatory and inhibitory synaptic input, regulate motor output (Powers et al 2012).…”
Section: Variability In Animals and Responses And Its Reduction By Nomentioning
confidence: 99%